Chemical and Molecular Assessment of Heavy Metal Residues and Meat Species Mislabeling in Meat Products from Tikrit City, Iraq - M Thalij, Karkaz; A Salman, Fatma; A Jasm, Mohammed (Journal of Meat Science, 2026)
Ensuring the safety and authenticity of meat products is a key public health priority, especially in areas with limited regulatory oversight. In Iraq, increasing demand for processed meats has raised concerns about contamination with toxic heavy metals and the mislabeling or adulteration of meat species. This study aimed to evaluate both the chemical safety and biological authenticity of commercially available meat products in Tikrit City markets by measuring heavy metals (Pb, Cd, and Al) levels and verifying species identity using molecular assays. A total of thirty meat samples, including commercial products and local minced beef, were analyzed. Heavy metal concentrations were determined after microwave digestion and inductively coupled plasma–mass spectrometry (ICP-MS). DNA was extracted from all samples and amplified with species specific mitochondrial primers (456 bp universal, 271 bp bovine, and 225 bp ovine), with agarose gel electrophoresis used to confirm the presence of bands. Data were statistically analyzed with ANOVA at a significance level of p<0.05. ICP-MS results showed widespread contamination with Pb and Cd, with many samples exceeding Codex Alimentarius and EFSA permissible limits. Pb levels ranged from 0.43 ± 0.03 mg/kg to 3.84 ± 0.74 mg/kg, while Cd levels ranged from 1.03 ± 0.05 mg/kg to 4.15 ± 0.14 mg/kg. Aluminum contamination varied from 1.1 ± 0.28 to 3.57 ± 0.82 mg/kg and was notably higher in processed products. PCR confirmed bovine DNA in most samples, while Bulgur Kibbeh contained sheep DNA, and Beef Kibbeh showed mixed bovine–ovine profiles. The combined chemical and molecular assessments reveal that meat products in Tikrit markets are often contaminated with hazardous levels of Pb and Cd. Additionally, PCR analysis uncovered occasional mislabeling and species substitution. These findings highlight urgent food safety issues in Iraqi markets and underscore the necessity for stricter regulatory oversight, improved hygienic practices, and routine use of molecular authentication tools to protect consumers and ensure accurate labeling.